Investigating the Retrofit of RC Frames Using TADAS Yielding Dampers - TahamouliRoudsari, Mehrzad; Cheraghi, K.; Aghayari, R. (Structural durability & health monitoring, 2022)
TADAS dampers are a type of passive structural control system used in the seismic design or retrofitting of structures. These types of dampers are designed so that they would yield before the main components of the structure during earthquake. This dissipates a large portion of the earthquake’s energy and reduces the energy dissipation demand in the main components of the structure. Considering its suitable performance, this damper has been the subject of numerous studies. However, there are still ambiguities regarding the effect of the number of these dampers on the retrofitting of reinforced concrete (RC) frames and their design procedure. In this study, a single-story, single-bay RC frame with the scale of 1:3, equipped with the TADAS damper, was subjected to hysteresis loading until the drift of 4%. Then, for further assessment, 48 calibrated numerical models were constructed in ABAQUS and the effects of the number of TADAS dampers and column axial force upon the stiffness, strength, and ductility of the frame were accurately investigated. Also, a number of formulations were presented to calculate how the stiffness and lateral strength of the retrofitted frame are affected by an increase in the number of the TADAS plates. The results showed that if the shear capacity of the retrofitted frame is three times that of the initial frame, the structure would have the best response. In addition, if the axial force in the columns exceeds 0.2 Pcr the energy dissipation and ductility factor of the frame drastically decrease.